(untitled) (Balthazar, 2022)
Animal sensibility is a central question in animal Aesthetics. In the following contribution, the issue of a special kind of aesthetic sensibility in the field of organic life is addressed from the viewpoint of the debate in French philosophy and in contemporary environmental philosophy. Starting with Étienne Souriau’s analysis of organic sensibility in his 1965 Le sens artistique des animaux, the question of a “double sensibility” in the broader field of organic life is addressed. Then, the issue of a special kind of artistic sensibility in animals and plants is linked to the “function” of animal artistry. In this sense, natural teleology is criticized by questioning the idea that every manifestation of artistic behaviours or aesthetically-relevant features is to be reconducted to its “usefulness” for the animal/plant. Then, animal artistry and artisticity is analyzed from the viewpoint of the debate concerning the anthropomorphic interpretation of animal behaviour. Finally, human and animal sensibility are interpreted as a kind of instict that is rooted in the very nature of organic life.